Preserving local culture as a strategy for sustainable tourism in Bali - Mudana, I Wayan; Sinaga , Firman; Suarja , I Ketut; Surata, I Ketut (YAYASAN MITRA PERSADA NUSANTARA, 2025)
Bali, as one of Indonesia’s most iconic tourist destinations, is globally celebrated for its rich cultural heritage, traditional arts, and spiritual practices. However, the rapid growth of mass tourism poses significant challenges to the preservation of local culture, potentially leading to cultural commodification and the erosion of community values. This article explores the role of cultural preservation as a strategic pillar for achieving sustainable tourism in Bali. Drawing on qualitative data from stakeholder interviews, local government policy reviews, and ethnographic observations in select Balinese villages, the study examines how traditional customs, rituals, and local wisdom can be integrated into tourism development frameworks. The findings reveal that preserving local culture not only enhances the uniqueness of Bali as a destination but also strengthens community identity, supports local economies, and fosters environmentally responsible tourism practices. Moreover, the involvement of local communities in tourism planning and cultural interpretation is identified as a critical factor in ensuring long-term sustainability. The paper proposes a model of culturally sustainable tourism that emphasizes collaboration between government institutions, private tourism operators, and indigenous communities. By aligning cultural preservation efforts with sustainable development goals (SDGs), Bali can mitigate the adverse impacts of overtourism while enhancing its global competitiveness. This research contributes to the broader discourse on sustainable tourism by demonstrating that safeguarding intangible cultural heritage is not merely a matter of cultural pride, but a pragmatic and necessary strategy for resilient tourism development. The insights offered may serve as a reference for policymakers, tourism stakeholders, and cultural practitioners seeking to balance economic growth with the protection of cultural authenticity in other heritage-rich destinations.